The Brave Little Puppy - Enid Blyton
When Clare and Martin find a little puppy struggling in a pond, they excitedly take it home to see if their mother will let them keep it. When two robbers try to steal the family's car, the brave pup shows how amazing he really is. Also in this collection are the stories of the very little hen, the runaway toys and the little pink pig. Other stories in this volume: A Cat in Fairyland The Enchanted Sea The Goblin Aeroplane The Runaway Toys Snifty's Lamp Post The Goldfish That Grew and many more...